Songs for a Little House - Morley, Christopher, 1890-1957 (Salt Lake City, UT : Project Gutenberg, 2007)
"Songs for a Little House" by Christopher Morley is a collection of light verse and poetry written in the early 20th century. The book reflects the warmth of domestic life, capturing moments of tenderness and everyday beauty, primarily focusing on family, home, and the simplicity of suburban living. The poems draw upon Morley's personal experiences, blending humor with nostalgia to depict the charm of ordinary life. In this collection, Christopher Morley presents a series of lyrical poems that explore themes such as love, domesticity, and the quiet joys of family life. Through various pieces like "Bayberry Candles," "The Young Mother," and "Washing the Dishes," Morley captures intimate moments shared between loved ones, offering reflections on childhood, parenthood, and companionship. The tone throughout is often whimsical and affectionate, creating a sentimentality that resonates with readers as he reminisces about the beauty found in the mundane aspects of daily life, all while maintaining an air of light-heartedness. (This is an automatically generated summary.)
Release date is 2007-10-25
E-text prepared by Ron Swanson
Keywords: Poetry